Sequence Characteristics and Phylogenetic Analysis of the Artemisia argyi Chloroplast Genome - Chen, Changjie; Miao, Yuhuan; Luo, Dandan; Li, Jinxin; Wang, Zixin; Luo, Ming; Zhao, Tingting; Liu, Dahui (Frontiers in Plant Science, 2022)
Artemisia argyi (A. argyi) is an important Asteraceae species with high medicinal value. There are abundant A. argyi germplasm resources in Asia, especially in China, but the evolutionary relationship of these varieties and the systematic localization of A. argyi in Asteraceae are still unclear. In this study, the chloroplast (cp) genomes of 72 A. argyi germplasm resources from 47 regions in China at different longitude, latitude or altitude, including wild and cultivated varieties were sequenced and the characteristics of cp genome were systematically analyzed. The cp genome size of A. argyi was about 151 kb and contained 114 genes, including 82 protein coding genes, 28 tRNA genes and four rRNA genes. And the number of SSRs in A. argyi cp genome ranged from 35 to 42, and most of them were mononucleotide A/T repeats. Moreover, a total of 196 polymorphic sites were detected in 72 A. argyi cp genomes, which could be used as DNA barcodes for variety identification. Phylogenetic analysis demonstrated that the genetic relationship between A. argyi varieties had little relationship with their geographical distribution in China. Furthermore, IR boundaries of ten Artemisia species were significantly different, which may serve as a marker to distinguish them. Moreover, sequence divergence analysis of 67 Asteraceae cp genomes showed that the variable regions were mostly located in single-copy (SC) regions, and coding regions were more conserved than non-coding regions. Moreover, the phylogenetic tree of 67 Asteraceae species constructed with 43 common protein coding genes showed better uniformity with traditional classification system, Artemisia species were grouped into one group, and A. argyi was closely related to Artemisia lactiflora and Artemisia montana. This study systematically analyzed the cp genome characteristics of the A. argyi, and compared cp genomes of Asteraceae species, which provided valuable information for identifying A. argyi varieties and understanding the evolutionary relationship of Asteraceae species.